Inovasi Perekonomian Digital dalam mengatasi Disparitas Regional Strategi Baru dalam Kebijakan Perekonomian di Indonesia - Suyanto Suyanto; Loso Judijanto; Agustiawan Djoko Baruno; Hadi Sugiyanto; Veronika Nugraheni Sri Lestari (IPM2KPE, 2024)
This research explores a new approach in Indonesia's economic strategy that specifically prioritizes digital economic innovation as a tool to address regional inequality. The background to the problem highlights the gaps in economic development in various regions in Indonesia and the importance of economic transformation through the use of digital technology. The literature study in this research presents a conceptual framework that describes the relationship between digital economic innovation, economic policy, and efforts to mitigate regional imbalances. The research process involved secondary data analysis, surveys, and interviews with relevant stakeholders. The research results show that the integration of digital economic innovation in economic policy has the potential to reduce regional imbalances by accelerating economic growth, creating job opportunities, and supporting market penetration for local companies. Conclusion, This research makes an important contribution to the development of future-oriented, data-based and technology-focused policies to address regional inequality, accelerate equitable economic growth and improve the welfare of the Indonesian population. Keywords: Regional Disparity, Economy, Digital Economy